2016
DOI: 10.1074/jbc.m115.708909
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Squamous Cell Carcinoma Cells Modulate Chemokine Expression and Hyaluronan Synthesis in Fibroblasts

Abstract: The aim of this study was to characterize the interaction of KYSE-410, an esophageal squamous cell carcinoma cell line, and fibroblasts with respect to the extracellular matrix component hyaluronan (HA) and chemokine expression. KYSE-410 cells induced the mRNA expression of HA synthase 2 (Has2) in normal skin fibroblasts (SF) only in direct co-cultures. Parallel to Has2 mRNA, Has2 antisense RNA (Has2os2) was up-regulated in co-cultures. Knockdown of LEF1, a downstream target of Wnt signaling, abrogated Has2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Accumulating evidence has demonstrated the crucial roles of chemokines and their receptors in tumor development and progression in several types of cancers (36)(37)(38)(39). Kretschmer and colleagues recently reported that esophageal SCC cells modulated chemokine expression in fibroblasts, affecting the tumor immune response (40). The most upregulated chemokine in F. nucleatumpositive esophageal cancers in the current study was CCL20.…”
Section: Discussionsupporting
confidence: 56%
“…Accumulating evidence has demonstrated the crucial roles of chemokines and their receptors in tumor development and progression in several types of cancers (36)(37)(38)(39). Kretschmer and colleagues recently reported that esophageal SCC cells modulated chemokine expression in fibroblasts, affecting the tumor immune response (40). The most upregulated chemokine in F. nucleatumpositive esophageal cancers in the current study was CCL20.…”
Section: Discussionsupporting
confidence: 56%
“…In all cases, this enriched stroma can support HAS2 expression in tumor cells as well as stromal cells . Interestingly, HAS2 is one of the primary enzymes regulated in cancer‐associated fibroblasts suggesting the possibility that tumor cells induce stromal cells to produce HA. In breast cancers, a high HA deposition in the stroma is related to lymph node positivity, poor differentiation, and poor patient survival .…”
Section: Role Of Hyaluronan Synthases In Malignancymentioning
confidence: 85%
“…The tumor microenvironment plays a key role in tumor development and progression [15,[22][23][24][25][26]. This dynamic environment is formed by several cellular components that include not only cancer cells, but also fibroblasts, and immune and endothelial cells [15].…”
Section: Structural Proteins and Ecm Stiffnessmentioning
confidence: 99%